The reptile room - Snicket, Lemony (Snicket, Lemony. Series of unfortunate events, 2007)
After narrowly escaping the menacing clutches of the dastardly Count Olaf, the three Baudelaire orphans are taken in by a kindly herpetologist with whom they live happily for an all-too-brief time.